Coach abusive supervision and athlete engagement: a moderated mediation model - Zeng, Yuan; Yin, Junjie (Frontiers in Psychology, 2025)
IntroductionAbusive supervision remains a prominent research focus in negative organizational behavior, yet existing findings remain inconsistent. Grounded in self-determination theory, this study examines the complex relationship between coach abusive supervision and athlete engagement, while investigating the mediating role of psychological empowerment and the moderating effect of athlete achievement motivation.MethodsUsing survey data from 152 athletes across Chengdu, Deyang, Mianyang, Yibin, and Zigong, we conducted hierarchical regression analyses to test: (1) the curvilinear association between abusive supervision and athlete engagement, (2) the instantaneous mediating effect of psychological empowerment, and (3) the boundary condition imposed by achievement motivation.ResultsKey findings revealed: (1) An inverted U-shaped relationship between coach abusive supervision and athlete engagement; (2) Psychological empowerment mediated this relationship, with abusive supervision and empowerment also exhibiting an inverted U-shaped pattern; (3) Athlete achievement motivation significantly moderated the curvilinear relationship between abusive supervision and engagement.DiscussionThis study elucidates the nonlinear transmission mechanism and psychological contingencies underlying athletes’ training engagement. The results offer theoretical contributions to sports organizational behavior literature while providing practical insights for coaches and sports administrators to optimize intervention strategies.